2019
DOI: 10.3390/molecules24132363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Sorbate and Ultrasonic Treatment on the Properties of Fish Scale Collagen/Polyvinyl Alcohol Composite Film

Abstract: Composite films containing different amounts of potassium sorbate (KS) were prepared by using fish scale collagen (Col) and polyvinyl alcohol (PVA). Fourier transform infrared spectroscopy (FTIR), light transmittance, mechanical, water vapor transmission rate (WVTR), and the antibacterial properties of the composite films were analyzed. The results showed that the addition of Col significantly reduced the light transmittance of the composite film, but KS had no significant effect on the light transmission. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, long-term intense ultrasonic treatment will destroy the structure of the polymer to a certain extent. Similarly, Liang et al [19] confirmed that with the increase of the ultrasonication time, the mechanical and barrier properties and of the film increased, but it has no significant effect on other properties. In addition, Liu et al [13] believed that ultrasonic treatment improved the barrier properties and degradability of polyvinyl alcohol (PVA)/TPs films, and the antibacterial rate of the films against E. coli and S. aureus was increased.…”
Section: Introductionmentioning
confidence: 82%
“…However, long-term intense ultrasonic treatment will destroy the structure of the polymer to a certain extent. Similarly, Liang et al [19] confirmed that with the increase of the ultrasonication time, the mechanical and barrier properties and of the film increased, but it has no significant effect on other properties. In addition, Liu et al [13] believed that ultrasonic treatment improved the barrier properties and degradability of polyvinyl alcohol (PVA)/TPs films, and the antibacterial rate of the films against E. coli and S. aureus was increased.…”
Section: Introductionmentioning
confidence: 82%
“…Fish scale collagen (Col) and polyvinyl alcohol (PVA) containing varying amounts of potassium sorbate (KS) were used to prepare composite films. The KS/Col/PVA films were found to have antimicrobial properties to be employed in food packaging (Liang et al., 2019).…”
Section: Biopolymers From Sfbpmentioning
confidence: 99%
“…It has been used since decades in the field of food technology and industry for its specific antifungal activities. Also, it can be used as a food additive for development of unique flavor of the food (Liang et al, 2019). However, the inhibitory effects of KS on shiga toxin producing E. coli are less informed.…”
Section: Introductionmentioning
confidence: 99%